Relevansi Konsep Upah Pengemudi Ojek Online Perspektif Yusuf Qardhawi - mira, humairah (ITB AAS INDONESIA Surakarta, 2024)
According to Yusuf Qardhawi, the concept of wages is that wages are determined based on an agreement between both parties. The wages given must be commensurate with the work and the workers' needs so that they can live a decent life in society. The aim of this research is to identify the relevance of the wage concept offered by Yusuf Qardhawi to the implementation of wages for Jasku Pamekasan online motorcycle taxi drivers. This research uses qualitative research, where the data is obtained from observations, interviews and documentation. The data obtained is used as material that is relevant to Yusuf Qhardawi's thinking. The results of this research explain that Jasku owners apply the concept of wages from Yusuf Qardhawi's perspective, namely the concept of fair and honest wages. Jasku's wage system uses a profit sharing system. The owner of Jasku announces the wage system in advance before work begins. The more diligent and active they are in their work, the more wages they will get.